160k views
2 votes
Solve for c. a (c+b)=d

2 Answers

5 votes

Answer:

c =
(d)/(a) - b.

Explanation:

a(c + b) = d

(c + b) = d / a

c + b =
(d)/(a)

c =
(d)/(a) - b.

Hope this helps!

User Fiehra
by
5.8k points
1 vote

Answer:


c = (d)/(a) - b

Explanation:

a( c + b ) = d

Divide both sides by a

That's


(a(c + b))/(a) = (d)/(a) \\ c + b = (d)/(a)

Move b to the right side of the equation to make c stand alone

We have the final answer as


c = (d)/(a) - b

Hope this helps you

User Edymerchk
by
5.2k points